2007
DOI: 10.1270/jsbbs.57.197
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Kinetin and Benzyl Adenine Plays a Vital Role in High Frequency Regeneration from Cotyledon Explants of Bottle Gourd (Lagenaria siceraria) in Relation to Ethylene Production

Abstract: The interaction between plant hormones throughout plant regeneration and development is complex. In the present study, we extended our investigation and disclosed the capacity of de novo shoot organogenesis from cotyledon explants of bottle gourd in relation to plant hormones and ethylene inhibitor. Synergistic effect of kinetin and benzyl adenine (BA) enhanced the shoot regeneration efficiency (80.6%) from cotyledon explants of bottle gourd, compared with BA or kinetin used separately, even in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
5
12
2
Order By: Relevance
“…Less fold difference is obtained on average shoot length of using TDZ instead of Kn, but with two fold higher concentration of TDZ than Kn. In contrast to our results, BAP was reported in literature as the most effective cytokinin for shoot induction and multiplication in cucurbits (Ananthakrishnan et al, 2003;Saha et al, 2007;Ganasan & Huyop, 2010) The percentage of regeneration using Kn is a at least a fold and half more than the percentage of regeneration using any of the other three types of cytokinin. After obtaining the highest physiological response, the percentage of regeneration is not inhibited much by increasing the concentration of cytokinin regardless of its type.…”
Section: Resultscontrasting
confidence: 99%
“…Less fold difference is obtained on average shoot length of using TDZ instead of Kn, but with two fold higher concentration of TDZ than Kn. In contrast to our results, BAP was reported in literature as the most effective cytokinin for shoot induction and multiplication in cucurbits (Ananthakrishnan et al, 2003;Saha et al, 2007;Ganasan & Huyop, 2010) The percentage of regeneration using Kn is a at least a fold and half more than the percentage of regeneration using any of the other three types of cytokinin. After obtaining the highest physiological response, the percentage of regeneration is not inhibited much by increasing the concentration of cytokinin regardless of its type.…”
Section: Resultscontrasting
confidence: 99%
“…Our study revealed that the effect of BAP and Kn combination on multiple shoot induction is more compared to BAP or Kn when used separately. This is in confirmation with the earlier studies in Bambusa glaucescens (Shirin and Rana, 2007) and Lagenaria siceraria (Saha et al, 2007). Srivastava and Joshi (2009) reported that BAP tested individually was more effective than Kn alone on shoot multiplication of Portulaca grandiflora but their combination was most advisable for shoot multiplication.…”
Section: Resultssupporting
confidence: 89%
“…In the present study our results revealed that the effect of BAP and auxin combination on multiple shoot induction is more compared to BAP or auxins when used separately. This is in confirmation with the earlier studies in Bambusa glaucescens (Shirin and Rana, 2007) and Lagenaria siceraria (Saha et al, 2007). For in vitro rhizogenesis, IBA at 2 mg/l concentration induced maximum number of roots while simultaneously improving the growth of micro shoots.…”
Section: Discussionsupporting
confidence: 92%